2021
DOI: 10.1101/2021.05.06.21256403
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of persistent SARS-CoV-2 IgG antibodies in oral mucosal fluid and upper respiratory tract specimens following COVID-19 mRNA vaccination

Abstract: Previous studies have shown that mRNA COVID-19 vaccines are highly effective at preventing SAR-CoV-2 infection by generating an immune response, which in part produces SARS-CoV-2 IgG antibodies in serum. In this study, we hypothesized that COVID-19 vaccines may elicit production of SARS-CoV-2 IgG antibodies in the upper respiratory tract, such as in oral and nasal mucosal fluid. To test that hypothesis, we enrolled 114 participants within 3-7 days of receiving the first dose of the Moderna mRNA COVID-19 vaccin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…As more and more people become vaccinated, we are using the lessons learned from this study to monitor the persistence of antibodies in oral mucosal fluids against the Moderna or Pfizer vaccine in an ongoing year long clinical trial. Our early results are encouraging as we observe an increasing antibody titer in vaccinated participants consistent with what we observed in this cohort ( 10 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As more and more people become vaccinated, we are using the lessons learned from this study to monitor the persistence of antibodies in oral mucosal fluids against the Moderna or Pfizer vaccine in an ongoing year long clinical trial. Our early results are encouraging as we observe an increasing antibody titer in vaccinated participants consistent with what we observed in this cohort ( 10 ).…”
Section: Discussionsupporting
confidence: 89%
“…To that end, OraSure Technologies ® has developed an oral specimen collection device (OSCD) and a total antibody ELISA for use with oral mucosal fluid collected from this device. An earlier study from our group showed that it is possible to quantify the antibody titers from oral mucosal fluids collected by the OSCD ( 10 ). It should be noted that, at present, the relationship between concentrations of antibody and possible immune protection is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Additionally, IgA and IgG neutralising antibodies, including highly effective secreted dimeric IgA, have been observed in the saliva of patients vaccinated with BNT162b1 or mRNA-1273. 15,[18][19][20] These studies show variable capacity among the parenteral vaccines to induce sterilising immunity at the mucosa, with ChAdOx1 vaccine being potentially less effective than the mRNA vaccines. Factors potentially influencing whether these vaccines induce mucosal sterilising immunity include the mechanism of the vaccine and the quantity and quality of circulating neutralising antibodies generated.…”
Section: Mechanisms Limiting Sars-cov-2 Infection and Replication Induced By Vaccination Effect Of Sars-cov-2 Vaccination On Infectionmentioning
confidence: 94%
“…Another key unanswered question is whether SARS-CoV-2 vaccination induces a B cell response in mucosal tissues. While SARS-CoV-2-specific antibodies are detectable in mucosal compartments such as the saliva and breast milk following vaccination, it is unclear whether these antibodies are a product of a local B cell response or how long they persist 166 168 . SARS-CoV-2 vaccines are administered intramuscularly and therefore are unlikely to induce sufficient levels of antigen expression or inflammation in mucosal tissues to support a local GC response.…”
Section: Concluding Remarks and Perspectivementioning
confidence: 99%